Therapist mindfulness and subjective vitality: the role of psychological wellbeing and compassion satisfaction. (2nd January 2021) - Martin-Cuellar, Ashley; Lardier, David T.; Atencio, David J.
Abstract: Background: Mindfulness and vitality are related constructs in the literature; however, mindfulness and vitality have not been fully examined in the literature, specifically with mental health therapists. Aims: This study aimed to investigate the relationship between mindfulness and vitality among a sample of licensed mental health clinicians. Compassion satisfaction (CS) and psychological wellbeing are further explored as mechanisms by which a therapist may experience vitality and the impact mindfulness may have on these mechanisms. Methods: Mediation analyses were utilized to understand the relationship between mindfulness and vitality and the indirect paths of psychological wellbeing and CS. Results: Results indicate that therapists with greater mindfulness report more vitality, higher overall psychological wellbeing and higher CS. As expected, the relationship between mindfulness and vitality was mediated by psychological wellbeing and CS. Results support the existing research on the relationship between mindfulness and vitality. Conclusions: Understanding the importance of psychological wellbeing and CS has implications for addressing the high incidences of the negative impact of therapeutic work.